THE CURRENT SCENARIO OF EDUCATION IN BRAZIL AND THE IMPLEMENTATION OF THE CIVIC-MILITARY EDUCATIONAL MODEL - Allison Santos, Allison; Sales Barbosa, Claudio; Henrique de Assis Brazil, Paulo; Farias Vitorino Brazil, Danielle; Paes de Lima Siqueira, Flávia; Steffane Silva de Lima, Djessyca (Revista Gênero e Interdisciplinaridade, 2021)
This study highlights an analysis of the current educational scenario in Brazil in the challenge of fostering new quality educational models, capable of raising the level of learning that will provide better opportunities for young people, with the consequent reduction of social inequality in the country. The Federal Government, then, aware of its role in this situation, through Decree No. 10.004, of September 5, 2019, launched the National Program of Civic-Military Schools, PECIM, which brings a management model in educational, didactic-pedagogical and administrative areas, in line with the Common National Curriculum Base (BNCC). The aim of this paper is to analyze the literature on the current educational scenario in Brazil from the standpoint of the implementation of the civic-military educational model. As a methodology, a basic and bibliographical research was chosen. For data collection, we used a literature review and analysis of primary bibliographic sources. Starting from the complex point of view of the issues discussed, dealt with and, above all, the data analyzed in the universe of this study, it was possible to formulate considerations, presenting a set of conclusions in an attempt to show the dimension of the view on the current scenario regarding the quality of education in public schools and the conception of the civic-military educational model. From the perspective of the right to quality education, the civic-military model can contribute to improving the behavior of students in the family, school and social environment. As well, it is understood that the partnership between the military bodies and the public school is relevant to significantly improve the quality of basic education with an emphasis on access, permanence and learning.